Regulating housing vacancies away? The paradoxical effects of mismatch - Paul Cheshire; Christian Hilber; Hans Koster (European Regional Science Association (ERSA), 2015)
Policy makers agree that vacant houses are undesirable. Moreover the existence of empty houses is used as an argument for allocating less land for new construction. So higher vacancy rates tend to trigger tighter restrictions on the supply of land. Such tighter restrictions lead to higher prices and, because of the incentives this creates for occupying housing, to lower housing vacancies (?opportunity cost effect?). There is, however, a second effect ignored by planners: more restrictive planning policies impede the matching process in housing markets so leading to higher vacancies (?mismatch effect?). Which of these two forces dominates is an empirical question. This is our focus here. Addressing potential reverse causation and other endogeneity concerns, we use a unique panel data set on land use regulation for 350 Local Authorities in England from 1981 to 2011. Our results show that tighter local planning constraints increase local housing vacancy rates, suggesting that the mismatch effect dominates. A one standard deviation increase in local regulatory restrictiveness causes the average local vacancy rate to increase by about 0.9 percentage points (23 percent). The results are economically meaningful and show that pointing to the existence of vacant houses as a reason for being more restrictive in allocating land for housing is counterproductive.
Keywords: R13; R38; 330; residential vacancy rates; housing supply constraints; land use regulation